TRÊS NOTÍCIAS SOBRE O IMPERADOR JULIANO: AMIANO MARCELINO, LIBÂNIO E SÃO GREGÓRIO DE NAZIÂNZIO - de Carvalho, Margarida Maria (PHOÎNIX, 2020)
I intend to show here some points of view of Amiano Marcelino, Libeinio e Seto Gregario de Nazianzo on the Emperor Julian. hi the same time I would like to introduce some ideas about the last two authors whose speeehs we have only in the present days in Brazil.